Romania : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This Selected Issues paper analyzes the developments and determinants of inflation in Romania, and reviews the salient trends in public finance. The study describes the monetary policy issues and the improvements required to clean up the financial sector. The paper chronicles the balance-of-payments crisis in 1999, the external viability trends, reviews the economic and financial implications, and assesses Romania's compliance with EU economic criteria. The paper also provides a statistical appendix for the country.